Dynamic Specification and Testing for Unit Roots and Co-Integration - Anindya Banerjee (Queen's University, Department of Economics, 1994)
This paper provides an interpretation of the vast literature on testing for unit roots and estimating co-integrating relations. Emphasis is placed on identifying the particular ways in which methods of dynamic specification need to be modified in order to take account of the possible presence of unit roots in the time series being modelled. The discussion is undertaken in the settings of both single-equation and systems methods and attention is paid to problems of estimation and inference. It is argued that the importance of issues such as exogeneity and rich dynamic specification, developed in the context of stationary time series, carry over to a very large extent when dealing with non-stationary series.
Keywords: C10; C13; C51; C52; 330; dynamic specification; co-integration; unit roots; exogeneity